TWO-STAGE TURBOCHARGING FOR MEDIUM-SPEED DIESEL ENGINE – A CONCEPT STUDY - Lundin, Kaj (My University, 2010)
The marine engine manufacturers have faced new challenges as the emissions legisla-tions are also becoming stricter in the marine sector. The future International Maritime Organization (IMO) marine engine regulations are aiming at significant reductions of nitrogen oxides (NOx) emissions. One method for reducing NOx emissions is to lower the combustion temperature by utilizing extreme Miller timing in combination with two-stage turbocharging. This method is of great interest as it is one of the few tech-niques that have the ability to reduce both NOx and carbon dioxide (CO2) emissions at the same time. The aim of this thesis was to do a concept study on two-stage turbocharging for a me-dium-speed diesel engine. The target was to find a feasible concept to be used in a six-cylinder Wärtsilä 46F in-line marine engine. The design process was started by defining the design targets. Various turbocharging system layouts were designed and evaluated according to the design targets. The most promising concepts were taken for further development and more detailed designs were made. The fact that a two-stage turbocharging system contains twice as many components compared to a single-stage system made the design work challenging. The target was to fit all of the components in approximately the same space as in a single-stage system so that the main dimensions would not increase notably. A compact and feasible concept was found. The chosen concept comprises of two axial turbine turbochargers which are located at the driving end of the engine. All of the main components are fastened to one turbocharger bracket. The main dimensions of the en-gine increased only slightly. Results from the natural frequency calculations were posi-tive. The natural frequencies were lower than on a standard engine, but still within ac-ceptable limits.
Keywords: Two-stage turbocharging; Miller-timing; Medium-speed diesel engine; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|